Mismatch between expectations and physical activity outcomes at six months following hip-arthroscopy: A qualitative study. (September 2020) - Jones, Denise M.; Kemp, Joanne L.; Crossley, Kay M.; Hart, Harvi F.; Ackerman, Ilana N.
Abstract: Objective: To explore factors influencing participation in physical activity for young to middle-aged patients at six months post-hip arthroscopy. Design: Qualitative study. Setting: Three specialist surgical centres in Australia. Participants: Seventeen adults aged 18–50 years. Main outcome measures: Individual semi-structured interviews were undertaken and transcribed verbatum. Inductive analysis of the data was undertaken, with themes identified through an iterative coding process. Results: Four key themes emerged from the analysis: 1) an evident mismatch between expectations and actual progress of physical activity during the first six months post-arthroscopy; 2) physical activity levels vary widely at six months post-operatively; 3) evidence of suboptimal psychological readiness to return to sport and an associated emotional toll; and 4) the influence of available support and information on post-operative physical activity. Conclusions: This qualitative study has provided in-depth perspectives on recovery after hip arthroscopy. Clear opportunities exist to: 1) help patients develop realistic post-operative goals; 2) provide timely patient education and support; and 3) facilitate an effective transition to desired physical activity. Highlights: A mismatch exists between patients' pre-operative expectations and post-operative recovery of physical activity. The discordance between expectations and actuality is a major source of anxiety for patients. Conflicting information from healthcare providers exacerbates anxiety. Physiotherapists are ideally placed to address modifiable barriers to an effective return to physical activity.